2017
DOI: 10.1266/ggs.16-00039
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nuclear mitochondrial DNAs and factors affecting patterns of integration in plant species

Abstract: Sequences homologous to organellar DNA that have been integrated into nuclear genomes are referred to as nuclear mitochondrial DNAs (NUMTs) and nuclear plastid DNAs (NUPTs). NUMTs in nine plant species were analyzed to reveal the integration patterns and possible factors involved. The cumulative lengths of NUMTs in two-thirds of species analyzed were greater than those of NUPTs observed in a previous study. The age distribution of NUMTs was similar to that of NUPTs, suggesting similar mechanisms for integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The nuclear integrants of organellar DNA were first discovered in a study in which a mitochondrial ATPase subunit gene was found in the nuclear genome, as well as in the mitochondrial genome of Neurospora crassa [25]. Since then, organelle-derived sequences were examined in the nuclear genome of a number of animals [26][27][28][29][30][31][32] and plants [15][16][17][18][19][20][21]. The availability of a large amount of plant organelle and nuclear genome data has made it possible to investigate the prevalence and characteristics of NUMTs and NUPTs in plants.…”
Section: Characterization Of Organellar Dna-derived Sequences In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear integrants of organellar DNA were first discovered in a study in which a mitochondrial ATPase subunit gene was found in the nuclear genome, as well as in the mitochondrial genome of Neurospora crassa [25]. Since then, organelle-derived sequences were examined in the nuclear genome of a number of animals [26][27][28][29][30][31][32] and plants [15][16][17][18][19][20][21]. The availability of a large amount of plant organelle and nuclear genome data has made it possible to investigate the prevalence and characteristics of NUMTs and NUPTs in plants.…”
Section: Characterization Of Organellar Dna-derived Sequences In Plantsmentioning
confidence: 99%
“…This makes the large-scale analysis of NUPTs and NUMTs in plants be possible. Currently, NUPTs and NUMTs in some plant genomes have been characterized [15][16][17][18][19][20][21]. The characterization of nuclear organellar DNAs in plants adds new insights into the role of NUPTs and NUMTs in genome structure and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the most important result seems to be the potential use of animal signal sequences for heterologous gene expression in plant cells, which will allow to evaluate the ancient endosymbiotic event results in a new light (Perry et al, 2006;Yoshida et al, 2017). Until now, this opportunity was clearly demonstrated only in studies performed solely in vitro (Luzikov et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The gene content and genome complexity of nuclear genomes differs among angiosperm taxa typically associated with these continuing intercompartmental DNA transfer events [12]. In contrast to those beneficial or nonfunctional long-existing nuclear organelle integrations, substantial numbers of newly formed norgDNA are more deleterious and are rapidly eliminated [14,15]. The pattern and mechanism of organelle-to-nucleus DNA transfer has been analyzed in detail in a number of species [16,17].…”
Section: Introductionmentioning
confidence: 99%